Compulsory care of individuals with severe substance use disorders and alcohol- and drug-related mortality: A Swedish registry study - Scarpa, Simone; Grahn, Robert; Lundgren, Lena M. (Frontiers in Psychiatry, 2023)
Aim: This study used 17 year of Swedish registry data (2003-2019) for 25,125 adults assessed for their severity of substance use to identify the baseline factors predicting the risk of being court-ordered into compulsory care and examine the association between admission to compulsory care and mortality risks due to alcohol- or drug-related causes. Methods and materials: Addiction Severity Index (ASI) assessment data were linked to register data on demographic characteristics, compulsory care admission and alcohol- and drug-related mortality. Cox regression models were used to identify baseline factors predictive of post-assessment admission to compulsory care in the five years post-substance use assessment. Discrete-time random-effect logistic regression models were used to examine the association between compulsory care duration and alcohol or drug-related mortality risks. Results: The first models identified that younger age, female gender, and ASI composite scores for drug use, mental health and employment were significantly associated with the risk of placement in compulsory care for drugs other than alcohol. Female gender and ASI composite scores for alcohol, drug use and employment were significantly associated with compulsory care treatment for alcohol use. The second models showed that older individuals and men were more likely to die due to alcohol-related causes, while younger individuals and men were more likely to die due to drug-related causes. Length of stay in compulsory care institutions significantly increased the likelihood of dying due to substance use-related causes. Conclusion: In Sweden, a significant concern is the higher likelihood of women and young individuals to be court-ordered to compulsory care. At the same time, our findings indicate that admission to compulsory care is not associated with a lower risk of substance use-related mortality. Factors such as compulsory care often not including any medical or psychological therapy together with relapse and overdose after discharge may be possible contributing factors to these findings.